Suspension Steady-State Kinematics and Compliance Analysis Based On Linear Bushing Model - Balakrishna Bhat, Abhishek; Naik, Akshay (My University, 2020)
The tuning of a suspension system involves balancing various parameters and demands. There is a need for analytical tools to get a better understanding of the suspension system and to speed up the design process. In the current thesis work, an analytical tool is developed and a methodology is established to understand the effect of elastic elements like bushings and springs on kinematic and compliance parameters. The tool will also later help in choosing optimum values of bushing stiffness in order to meet the required kinematic and compliance targets. In the first step, the position constraints and force constraints of the 5 link suspension system are modelled along with bushing elements. The bushings are modelled as a tensor with the possibilities of adjusting the bushing orientation. By using Newton Forward Euler method and non linear solver, the static equilibrium of the system at a corresponding wheel force input can be determined. This also includes the movement of the hardpoints in the suspension system during jounce, rebound and steering motions. Further the methodology is implemented to a Four link suspension and an Integral link suspension. Sensitivity analysis is another important application of the tool. The system comprises of many bushings and sensitivity analysis is performed to understand the contribution of each bushing for a particular design parameter like toe change, camber change, brake steer, lateral force steer and so on. For the sensitivity analysis, the non linear system is linearized at small displacements and a governing equation is formulated. The governing equation consists of the stiffness matrix to map the effects of the elastic elements in the system and the constraint Jacobian to describe the velocity constraints of the system. The process of tuning is further optimized with the help of multi-objective optimization techniques. In order to meet design targets, the process of changing the bushing stiffness individually can be time consuming. With the help of the optimization tool, the optimum values of the bushing stiffness to meet the kinematic targets can be calculated automatically based on the required wheel motion. This will save significant time during the tuning process. In order to corroborate the established methodology, the mathematical models are later verified with multi body dynamics simulation software MSC ADAMS Car. It is found that the results from the developed mathematical models have a very good match with results from MSC ADAMS Car. The developed methodology has been successfully implemented for a Five link, Four link and an Integral link suspension system. The tool also has a wide range of applications.
Keywords: Five link suspension; Integral link suspension; Four link suspension; Elastokinematic analysis; Non linear solver; Bushing optimization; Force distribution; Multi-body dynamics simulation